Prescriptive Design Standards for Resilience of Canadian Housing in High Winds - Stevenson, Sarah A.; Kopp, Gregory A.; El Ansary, Ayman M. (Frontiers in Built Environment, 2020)
High-wind events cause significant damage to structures and property; in particular, light-frame wood homes are especially vulnerable and are the most abundant housing type in North America. As with many regions, Canadian homes are built to prescriptive standards that are based on historical construction methods and have remained relatively unchanged structurally across several decades, even though energy requirements have changed substantially. The present work reviews existing recommendations and campaigns for wind resilience in other jurisdictions, assesses their relevance to the Canadian context, and evaluates current construction methods as well as proposed improvement alternatives. Components that are commonly observed to fail in Canadian tornado damage surveys are of primary interest; namely, roof sheathing, roof-to-wall connections, and discontinuities in wall-to-floor links. Limit states design-based calculations are completed to assess the adequacy of nailed components from an engineering design standpoint. Past work quantifying the inadequacy of roof sheathing provisions in the current version of the National Building Code of Canada is discussed, and new analyses are done for the other components. Sources of conservatism in design calculations are identified, and unfactored results are provided to describe more representative limit states. When the redundancy of load and resistance factors is removed, the results show that current prescriptive provisions for roof-to-wall fasteners are likely to be sufficient up to a failure wind pressure of about 0.6 kPa – this applies to most regions in Canada. The wall capacity calculations suggest significant vulnerability to uplift or sliding withdrawal of nailed connections; however, these results are considered to be especially conservative. Potential, non-structural sources of house capacity are discussed. In general, current prescriptive provisions are deemed suitable for the synoptic wind events that they are expected to face. However, concern is identified for houses in open terrain or those prone to tornado risk. Design recommendations are presented in the context of providing resistance to up to EF2 tornadoes.